Purification of Trypanosoma cruzi metacyclic trypomastigotes by ion exchange chromatography in sepharose-DEAE, a novel methodology for host-pathogen interaction studies (2017)
Metacyclic trypomastigotes are essential for the understanding of the biology of Trypanosoma cruzi, the agent of Chagas disease. However, obtaining these biological stages in axenic medium is difficult. Techniques based on charge and density of the parasite during different stages have been implemented, without showing a high efficiency in the purification of metacyclic trypomastigotes. So far, there is no protocol implemented where sepharose-DEAE is used as a resin. Therefore, herein we tested its ability to purify metacyclic trypomastigotes in Liver Infusion Triptose (LIT) medium cultures. A simple, easy-to-execute and effective protocol based on ion exchange chromatography on Sepharose-DEAE resin for the purification of T. cruzi trypomastigotes is described. T. cruzi strains from the Discrete Typing Units (DTUs) I and II were used. The strains were harvested in LIT medium at a concentration of 1 × 107 epimastigotes/mL. We calculated the time of trypomastigotes increment (TTI). Based on the data obtained, Ion exchange chromatography was performed with DEAE-sepharose resin. To verify the purity and viability of the trypomastigotes, a culture was carried out in LIT medium with subsequent verification with giemsa staining. To evaluate if the technique affected the infectivity of trypomastigotes, in vitro assays were performed in Vero cells and in vivo in ICR-CD1 mice. The technique allowed the purification of metacyclic trypomastigotes of other stages of T. cruzi in a percentage of 100%, a greater recovery was observed in cultures of 12 days. There were differences regarding the recovery of metacyclic trypomastigotes for both DTUs, being DTU TcI the one that recovered a greater amount of these forms. The technique did not affect parasite infectivity in vitro or/and in vivo. © 2017 Elsevier B.V.